Brill's companion to the reception of Plato in antiquity - Tarrant, Harold.; Layne, Danielle A.; Baltzly, Dirk.; Renaud, François. (Brill's Companions to Classical Reception, 2018)
Brill's Companion to the Reception of Plato in Antiquity offers a comprehensive account of the ways in which ancient readers responded to Plato, as philosopher, as author, and more generally as a central figure in the intellectual heritage of Classical Greece, from his death in the fourth century BCE until the Platonist and Aristotelian commentators in the sixth century CE. The volume is divided into three sections: 'Early Developments in Reception' (four chapters); 'Early Imperial Reception' (nine chapters); and 'Early Christianity and Late Antique Platonism' (eighteen chapters). Sectional introductions cover matters of importance that could not easily be covered in dedicated chapters. The book demonstrates the great variety of approaches to and interpretations of Plato among even his most dedicated ancient readers, offering some salutary lessons for his modern readers too.